Mechanism of action of dichloro-beta-D-ribofuranosylbenzimidazole: effect on in vitro transcription. - Zandomeni, R (1982)
The adenosine analog 5,6-dichloro-1-beta-D-ribofuranosylbenzimidazole (DRB) and its mono- and triphosphate derivatives inhibit RNA polymerase II-specific transcription in an extract of whole HeLa cells. The analog does not inhibit RNA polymerase III-specific adenovirus VA RNA transcription in the whole cell extract. With purified RNA polymerase II under nonspecific transcription conditions, no effect on DRB could be detected. DRB is equally effective in inhibiting in vitro transcription from several of the adenovirus promoters and the human epsilon-globin gene. The inhibitory effects are in the order DRB greater than DRB monophosphate greater than DRB triphosphate. Thus DRB acts in vitro presumably on systems in which specific RNA polymerase II initiation of transcription occurs and with no detectable effect on premature termination. This will provide a suitable model for study of the molecular mechanism of action of DRB on transcription.